Understanding the impact of influencers on social media upon consumer purchasing decisions - Amaragiri, Anneli (2018)
The purpose of this dissertation is to understand the role that influencers play in relation to consumer purchasing decisions and consumer attitudes towards this. In order to understand this, influencers have been separated and identified as either traditional influencers; those who have amassed a following through traditional media such as television or music; or non-traditional influencers; those who have gained a following primarily through the increasing popularity of social media.